Skills and occupational mismatch in Malaysian labour market - Jamaludin, Salwaty (2021)
Despite its low unemployment rate, Malaysian labour market is currently sending signals of mismatch: a misallocation between demand and supply in the labour market. The issue of mismatch should not be ignored as it indicates the incapability of economies to employ their existing stock of human capital, and impeding long-term productivity. Motivated by the above issue, this study attempts to measure the level of mismatch and its factors. Specifically, the aims of this study are threefold. The first objective is to measure skills mismatch and its contribution towards mismatch unemployment in Malaysia by using annual data 2006-2017 from the Department of Statistics Malaysia (DOSM), Ministry of Human Resource Malaysia (MOHR), and Bank Negara Malaysia (BNM). The result reveals that in 2007, the index was only 0.108, while in 2017, it surged up to 0.273, which indicates there is 27% of hires were lost due to misallocations in the labour market. Mismatch unemployment has contributed around 50% to the rise of the unemployment rate. This suggests that the formal education system in Malaysia is not responsive to the demands of the labour market and vice versa. The second objective measures occupational mismatch by quantifying the level of overeducated and undereducated workers in the labour market. It was measured using both Job Analysis and Realized Matches methods, employing 2010-2015 Labour Force Survey (LFS) data. The analysis suggests undereducated workers are more prevalent in the labour market. On average, the level of undereducation was 0.338, which means that 34% of the labour force were undereducated. However, the proportion of severely overeducated workers have been rising year by year. Among occupations, technicians and associate professionals, and clerical support workers are the ones in which there is the highest proportion of overeducated. Among sectors, agriculture, forestry and fishery, construction, and administrative and support service activities are the ones in which there is the highest proportion of mismatch. The third objective, survey fieldwork was carried out to identify supply-side factors of mismatch. A total of 402 questionnaires were gathered from a stratified random sample of unemployed graduates in career fairs. Using the Relative Importance Index (RII), the findings reveal that in general, job seekers believe that no jobs are available in the market. This circumstance at least indicates the disconnection between the demand and supply sides, as information on job vacancies of the former fails to reach the latter. This study makes a significant contribution to the study of unemployment in two ways. First, it proposes new tools to measure the mismatch, specifically skills mismatch index, mismatch unemployment, and occupational mismatch level in Malaysia. Although mismatch remains a challenge and a top policy concern, there has been no systematic mismatch measurement analysis. Another contribution is that by understanding the reason for unemployment, policy makers could enhance an active labour market policy to avoid human capital destruction.